2021
DOI: 10.3390/bs11100131
|View full text |Cite
|
Sign up to set email alerts
|

Meaning-Making Coping Methods among Bereaved Parents: A Pilot Survey Study in Sweden

Abstract: The death of a child may result in traumatizing forms of grief, and meaning-making coping with loss seems to be important in prevention of intense psychosocial problems among bereaved parents. The aim of this quantitative pilot study was to discover the divergent meaning-making coping methods used by bereaved parents in Sweden. In doing so, 162 respondents were selected using a convenience sampling method, and they responded to the modified version of RCOPE. The study revealed that the strategies talking to ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(43 reference statements)
1
7
0
1
Order By: Relevance
“…Several studies ( Ahmadi et al, 2021a ; Ahmadi, 2006 , 2015 ; Ahmadi et al, 2021b ; Ahmadi and Zandi, 2021 ; la Cour and Hvidt, 2010 ; la Cour et al, 2012 ) have shown that, in countries like Sweden or Denmark where people have internalized secular norms and values, when informants maintain that they are spiritual, this sometimes implies that they are neither religious nor atheists. For instance, studies have shown that, in some strong secular countries, when people say they believe in a higher power, they often are not referring to God.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies ( Ahmadi et al, 2021a ; Ahmadi, 2006 , 2015 ; Ahmadi et al, 2021b ; Ahmadi and Zandi, 2021 ; la Cour and Hvidt, 2010 ; la Cour et al, 2012 ) have shown that, in countries like Sweden or Denmark where people have internalized secular norms and values, when informants maintain that they are spiritual, this sometimes implies that they are neither religious nor atheists. For instance, studies have shown that, in some strong secular countries, when people say they believe in a higher power, they often are not referring to God.…”
Section: Discussionmentioning
confidence: 99%
“…The modified RCOPE used in the present study had a Cronbach’s Alpha value of 0.794 (high), included 15 items, and it was rated on a 4-point Likert scale ranging from 0 (“Never”) to 3 (“Very often”); an additional 10 background items were also added to the questionnaire. The instrument was validated for form, language, and content in earlier studies ( Ahmadi et al, 2018 ; Ahmadi et al, 2021a ; Ahmadi and Zandi, 2021 ). These studies also reported a very high reliability coefficient for this questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The modified RCOPE had a Cronbach's alpha of 0.742 (high) and comprised 15 items rated on four-point Likert scales ranging from 0 (“Never”) to 3 (“Very often”); also, 10 background items were added to the questionnaire ( Appendix 1 ). The scale was validated for content and form in previous research ( Ahmadi & Zandi, 2021 ; Ahmadi et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, many people use non-religious or non-spiritual coping methods, for example, drawing on nature or “internal power”, which are existential and involve meaning-seeking. Such methods were identified by an international research effort in nine cultural settings ( Ahmadi, 2006 ; Ahmadi & Ahmadi, 2018 ; Ahmadi et al, 2016 , 2018 ; Ahmadi & Zandi, 2021 ) and by other research as well ( la Cour et al, 2012 ; McDougle et al, 2016 ). The term “existential coping” is applied to these methods of coping with crisis, because they represent attempts to find internal (e.g., in nature, themselves, or others) rather than transcendent (i.e., in God) resilience.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A particular aspect of bereavement is trauma, and recent experiences related to the COVID-19 pandemic have created a considerable number of people affected by this type of loss. The article “Meaning-Making Coping Methods among Bereaved Parents: A Pilot Survey Study in Sweden” [ 15 ] introduces the theme of trauma related to deaths caused by COVID-19. Likewise, the article “A Scoping Review of Interventions for Family Bereavement Care during the COVID-19 Pandemic” [ 16 ] summarizes findings from the existing literature regarding bereavement support interventions (i.e., psychosocial and psychotherapeutic interventions) for family caregivers of people who died of COVID-19.…”
Section: On Loss Bereavement and The Covid-19 Pandemic Crisismentioning
confidence: 99%